2020
DOI: 10.1038/s41598-020-61695-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic landscape of autism spectrum disorder in Vietnamese children

Abstract: Autism spectrum disorder (ASD) is a complex disorder with an unclear aetiology and an estimated global prevalence of 1%. However, studies of ASD in the Vietnamese population are limited. Here, we first conducted whole exome sequencing (WES) of 100 children with ASD and their unaffected parents. Our stringent analysis pipeline was able to detect 18 unique variants (8 de novo and 10 ×-linked, all validated), including 12 newly discovered variants. Interestingly, a notable number of X-linked variants were detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 100 publications
0
11
1
Order By: Relevance
“…Variant calling and annotation were performed based on highly regarded tools 28 . Reads with low quality, adapters and noise were removed prior to the downstream analysis by using FastQC and Trimmomatic.…”
Section: Methodsmentioning
confidence: 99%
“…Variant calling and annotation were performed based on highly regarded tools 28 . Reads with low quality, adapters and noise were removed prior to the downstream analysis by using FastQC and Trimmomatic.…”
Section: Methodsmentioning
confidence: 99%
“…In this sense, the causes of ASD might be considered highly genetic due to multiple patterns of family inheritance and the occurrence of many variations. It is currently known that men have a higher incidence of ASD, about four times more than women [16].…”
Section: Genetic and Environmental Contributorsmentioning
confidence: 99%
“…Remarkable advances in the knowledge of ASD risk factors have revealed that genetic mutations are among the main factors involved in alterations of the cell and molecular processes ( Figure 1 ) ( 26 ). According to preclinical and clinical studies, over 800 ASD-related genes have been reported ( 27 ), of which about 100 genes are significantly correlated with the development of autism-related behaviors ( 28 ). For instance, AVPR1a, DISC1, DYX1C1, ITGB3, SHANK3, SLC6A4, RELN, and RPL10 are among the genes which are implicated in the metabolic alterations related to the brain in ASD patients ( 29 ).…”
Section: An Overview On Pathophysiology Of Autism Spectrum Disordermentioning
confidence: 99%